A review on the production of grinding tools through additive manufacturing processes: From current possibilities to future perspectives - Borges, Diego Jorge Alves; Souza, Adriel Magalhães; da Silva, Eraldo Jannone (Machining science and technology, 2023)
Additive manufacturing (AM) processes have emerged as alternatives for the production of grinding tools. This article addresses a comprehensive overview on the historical-scientific evolution of the AM production of grinding/abrasive tools and provides future trends in the field. Bibliometric and systematic reviews of the literature verified the technological frontiers of each AM method, indicating current possibilities and potential gaps for future perspectives.